1992
DOI: 10.1089/aid.1992.8.9
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Human Immunodeficiency Virus Fusion Peptides. Analysis of Interrelations Between Their Structure and Function

Abstract: The N-terminal region of the human immunodeficiency virus type 1 (HIV-1) gp41 appears to be involved in virus-cell membrane fusion. To study the influence of fusion domain structure on gp41 interaction with artificial lipid membranes, two families of peptides were synthesized. The peptides of the first family starting from the C-terminal Gly-532 of gp160 (BRU isolate) were assembled in a stepwise manner to N-terminus of gp41(Ala-517). These hydrophobic peptides, containing 10-16 amino acid residues (a.a.), wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
35
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 26 publications
3
35
0
Order By: Relevance
“…Rafalski et al [6] showed destabilization of POPG liposomes and membrane mixing of small sonicated vesicles. Slepushkin et al [7] showed the ability of a family of gp41 peptides to cause increased conductance of planar lipid bilayers, liposome lysis and lipid mixing. The HIV-1 fusion peptide has been shown to induce lysis of human erythrocytes and CD4 ÷ lymphocytes [8].…”
Section: Introductionmentioning
confidence: 99%
“…Rafalski et al [6] showed destabilization of POPG liposomes and membrane mixing of small sonicated vesicles. Slepushkin et al [7] showed the ability of a family of gp41 peptides to cause increased conductance of planar lipid bilayers, liposome lysis and lipid mixing. The HIV-1 fusion peptide has been shown to induce lysis of human erythrocytes and CD4 ÷ lymphocytes [8].…”
Section: Introductionmentioning
confidence: 99%
“…The fusion peptide is likely to insert into the target lipid bilayer, making gp41 capable of interacting simultaneously with the viral and cell membranes (5,8,12,13,25,39). The involvement of this conserved hydrophobic segment of about 25 amino acids in triggering fusion is supported by prediction (13,15,40), mutational analysis (2,10,11,35), and in vitro studies carried out using synthetic peptides and model membranes (16,20,23,(27)(28)(29)(30)(31)36). Fusion peptides inserted into the target membrane might drive the aggregation of gp41 trimers at initial sites of fusion as well (39).…”
mentioning
confidence: 98%
“…Our present understanding of FP structure and function is based on FP-containing fragments amenable to chemical synthesis. The tendency of free FP-containing fragments to aggregate in solution is well documented (17)(18)(19)(20)(21). However, their highly hydrophobic nature suggests they target or interact with membranes.…”
mentioning
confidence: 99%